O hidropatrimônio a partir da análise integrada da paisagem em Canindé de São Francisco e Pirambu, Sergipe - Mello, Rodrigo Souza (2023)
Hydropatrimony is a set of water elements that have scientific, educational, and cultural values, making them subject to protection. This portion of geodiversity is considered a natural heritage, being the basis of life on planet Earth, and its quality is one of the main factors that influence its valuation. Understanding the environmental and territorial dynamics surrounding water is essential to identify hydrological sites of interest and develop strategies for their conservation. One of the main challenges related to different types of water use is monitoring and analyzing its quality. The lack of studies can have negative impacts on the health of the population that consumes contaminated water, as well as affect biodiversity and aquatic ecosystems. Another point to consider is the relationship between disorganized leisure activities and the loss of the geodiversity elements that make up the hydropatrimony. This loss can have negative impacts on the landscape and biodiversity, as well as affect the quality of water and compromise the different economic and social uses of water in the territory. This research aims to analyze the hydropatrimony of the municipalities of Canindé de São Francisco/SE and Pirambu/SE from the perspective of the GTP, in order to understand territorial and environmental dynamics, characterize the spatial research scope, and identify Hydrological Sites of Interest (LIH). The methodology used to achieve the proposed objectives corresponds to the proposals of Foleto and Costa (2021) and Simic; Milovanovic; Glavonjic (2014), associated with field activities and the use of geotechnologies. The evaluated locations were the Lajedão Waterfall in Canindé de São Francisco and the Roncador Waterfall and Redonda Lagoon in Pirambu. However, these locations did not meet the minimum evaluation criteria to be considered Hydrosites, with ecological criteria being the main factor for non-classification. Based on the identification of potentialities and tensions present in the LIH, geoconservation strategies were weighted for the LIH areas, aiming to improve the evaluated criteria. It was concluded that the creation and execution of actions related to geoconservation that understand the environmental and territorial dynamics related to different water uses are necessary, in order to preserve its quality, as well as strengthening integrated and participatory water resource management.